Child's play [videorecording (DVD)] - Holland, Tom, 1943-; Holland, Tom, 1943-; Hicks, Catherine, 1951-; Sarandon, Chris; Vincent, Alex, 1981-; Dourif, Brad, 1950-; Manoff, Dinah (MGM DVD : Distributed by Twentieth Century Fox Home Entertainment, 2008)
Six-year-old Andy is thrilled when he gets a brand-new cheery Chucky doll for his birthday. But he quickly discovers that Chucky is possessed by the soul of a notorious serial killer who swiftly begins terrorizing Andy, his ill-fated babysitter and his disbelieving mom. And he doesn't stop there. Proving he's nobody to toy with, the demonic doll schemes to transfer his evil spirit out of its "kid-friendly" container-- and into Andy.